Capturing Opportunities in the Industrial Revolution 4.0: E-Commerce, Digital Marketing, Prestige, and Instant Online Buying - Wibowo, Bambang Setia; Haryokusumo, Diaz (JDM (Jurnal Dinamika Manajemen), 2020)
This study aims to examined the effect of e-commerce, digital marketing, and consumer prestige on instant online buying decisions with perceived quality as an intervening variable on millennial generation. This research used survey design with purposive sampling. This research was conducted on 152 students in Yogyakarta who had already done online shopping in the marketplace. Data analysis was performed using Structural Equation Model (SEM) using Analysis Moment Structure (AMOS). This research proves that there is a positive influence on the use of e-commerce, digital marketing, and prestige on instant online buying decisions of consumers with perceived quality as an intervening variable on millennial consumers. The direct factor that influences instant online buying decisions is perceived quality, while e-commerce, digital marketing and prestige have an indirect effect on instant online buying because they have to pass through perceived quality. Theoretical and practical implications are discussed later.